Le contrat comme technique de participation des citoyens aux décisions en matière énergétique - Guibal, Michel (Les Cahiers de droit, 1983)
Contractual techniques have known a remarkable development in French administrative law. Contractual relations between different government agencies and individuals have reflected a change in the relationship between the State, central agencies and corporations on one side, and local authorities, associations and individuals on the other. « Inequality, Hierarchy and Government Supervision » have been partially replaced by « Equality, Participation and Autonomy ». In this article, the author describes some instances where contractual techniques were used to promote the participation of local interests in energy decisions. He points out the consequences of such a technique of participation and concludes that its main problem is the representativeness of the participants